2017
DOI: 10.4317/jced.53434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orthodontic treatment involving first premolar extractions on mandibular third molar angulation and retromolar space

Abstract: BackgroundThird molars present more problems than other teeth because they are the last teeth to erupt, and so it is important to assess their development when designing an orthodontic treatment plan. The aim of this study was to compare the angulation of the mandibular third molar and retromolar space before and after orthodontic treatment in cases involving first premolar extraction.Material and Methods76 patients, 59 women (77.63%) and 17 men (22.36%), were recruited from the Orthodontics Clinic at Beneméri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…20 In contrary to the above studies significant relationship was observed between the initial age of the patient and the amount of change in the inclination of the third molar in a study by Schiller et.al. 21 There is gender-specific variations in the angulation of third molars, demonstrating a higher degree of verticalization in women compared to men 22 As with previous M3 studies, the present study did not reveal a basis to predict the eruption of M3. 23 In a study conducted by Al kuwari etal it was concluded that the orthodontic treatment involving first premolar extraction has shown improvement in the angulation of third molars during eruption, thereby supporting the implementation of orthodontic extraction therapy in borderline cases.…”
Section: Discussionsupporting
confidence: 48%
“…20 In contrary to the above studies significant relationship was observed between the initial age of the patient and the amount of change in the inclination of the third molar in a study by Schiller et.al. 21 There is gender-specific variations in the angulation of third molars, demonstrating a higher degree of verticalization in women compared to men 22 As with previous M3 studies, the present study did not reveal a basis to predict the eruption of M3. 23 In a study conducted by Al kuwari etal it was concluded that the orthodontic treatment involving first premolar extraction has shown improvement in the angulation of third molars during eruption, thereby supporting the implementation of orthodontic extraction therapy in borderline cases.…”
Section: Discussionsupporting
confidence: 48%
“…The majority of previous findings reported that premolar extraction did not affect M3–M2. 14 , 17 , 18 , 19 , 20 , 35 , 36 Although the mandibles can keep growing until age 25, their growth rate substantially reduces in the postpubertal period, and the bone almost reaches its maximum size at approximately 18 years. 37 A longitudinal study reported that unerupted M3 generally remained in an impacted condition, and the angulation slowly increased by approximately 20° after 12 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 16 However, the results were controversial because of the variety of demographic characteristics (eg, age, sex), evaluation methods, biomechanics of the orthodontic treatment, and characteristics of the PE group. Most previous studies reported that premolar extraction did not affect M3 angulation measured by either M3–M2 angle 17 , 18 , 19 , 20 or M3–occlusal plane (M3–OP) angle. 17 , 19 Contrarily, M3–M2 angle, 21 M3–horizontal plane (M3–HP), 22 and M3 eruption space 17 , 19 , 23 were found to improve in studies with carefully selected orthodontic cases.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This impacted condition may cause several pathological conditions including carious lesions in the adjacent tooth, pericoronitis, periodontal conditions, odontogenic or dentigerous cysts, and tumors and external root resorption (ERR) of second molars. [1][2][3] ERR of lower second molars, considered as pressure resorption, is a pathological process caused by LITM, the action of orthodontic appliances, chronic periapical periodontitis, dental trauma, cysts, and tumors. The incidence of ERR in lower second molars caused by LITM is not prevalent as cited in several previous studies 4 wherein its incidence varies from 3.05% to 24.2%.…”
Section: Introductionmentioning
confidence: 99%